Experimental studies on the effect of metal oxide and antioxidant additives with Calophyllum Inophyllum Methyl ester in compression ignition engine. (10th November 2017) - Ashok, B.; Nanthagopal, K.; Subbarao, Rayapati; Johny, Ajith; Mohan, Aravind; Tamilarasu, A.
Abstract: Biodiesels derived from the seeds of Calophyllum Inophyllum plants offer to be commercially viable alternative to conventional fossil fuel which can make compression ignition engines technologically cleaner. The fuel properties of biodiesel obtained are similar to that of diesel and are found in abundance in southern India, which makes it more commercially viable alternative to fossil fuels. Also, with the presence of additional oxygen molecules within the fuel itself, the hydrocarbon (HC) and carbon monoxide emissions associated with biodiesel are lower compared to conventional fossil fuels with only exception to oxides of nitrogen emissions. In the present work, the effect of two fuel additives namely, titanium dioxide(TiO2 ) nanoparticle and butylated hydroxytoluene(BHT) on Calophyllum Inophyllum biodiesel is studied by observing the performance, emission and combustion characteristics on a twin cylinder CI engine. Results obtained from the experiments show that the nanoparticles are capable of enhancing the combustion process and they also act as an oxidizing catalyst. Dispersion of 100 ppm of TiO2 nanoparticle resulted in the improvement of brake thermal efficiency by 4% at full load condition along with comparable reduction in emission levels. The tendency of BHT to inhibit the formation of free radicals also produces marginal improvement in performance characteristics and is found to be more effective in mitigating NOx emissions, but adversely affecting HC and CO emissions. Addition of 500 ppm of BHT to biodiesel results in 11.65% reduction of NOx emissions at full load condition. Overall, the antioxidant provides better output in NOx mitigation with the slight reduction of performance as compared to the metal oxide nanoparticle. Highlights: Effect of antioxidant and metal oxide additives with Calophyllum Inophyllum is studied. Different concentration of Titanium dioxide and BHT are added with biodiesel. Performance and combustion output is better for the additives of nanoparticle. Addition of nanoparticles reduces the CO, HC and smoke emissions more effectively. Antioxidant shows a better NOx reduction capability than the nanoparticle.